Harnessing freshwater snails to enhance water quality and sustainability in integrated multi-trophic prawn farming systems, Bangladesh - Alif Layla Bablee; Mohammad Mahfujul Haque; Md. Mehedi Alam; Md. Zahid Hasan; Abdullah Al Rakib; Nusrat Jahan Tarin; Md. Ismail Hossain; Niels O. G. Jørgensen; Lars Hestbjerg Hansen (Molluscan Research, 2026)

A preliminary field-based assessment of greenhouse gas emissions from prawn aquaculture ponds in Bangladesh: effects of farm management and water quality - Abul Bashar; Richard D. Heal; Md. Zahid Hasan; Abdullah Al Rakib; Md. Ainuddin; Md. Mehedi Alam; Alif Layla Bablee; M. M. R. Jahangir; Niels O. G. Jørgensen; Lars Hestbjerg Hansen; Mohammad Mahfujul Haque (Aquaculture International, 2026)
Greenhouse gas (GHG) emissions from coastal aquaculture are an emerging environmental concern, with implications for ecosystem sustainability and climate mitigation. In this preliminary field-based study, we quantified carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous dioxide (N 2 O) fluxes from 35 randomly selected prawn farms in coastal Bangladesh, at a single time point using the floating chamber method, with concurrent water quality monitoring and farm management surveys, to identify key factors influencing in-pond GHG emissions. Extensive farming systems showed a higher CO 2 emission rate (1261.3 ± 727.0 g/ha/day) than semi-intensive farms, while CH 4 (10.3 ± 5.60 g/ha/day) and N 2 O (0.71 ± 0.53 g/ha/day) fluxes were higher in the semi-intensive farms. The total GHG emissions (CO₂ equivalent; CO₂e in a 100-year life span) were lowest in semi-intensive farms (898.3 ± 245.7 g/ha/day). Correlation analysis revealed significant negative associations between total CO 2 e emissions and salinity, feeding frequency, and carp stocking density, while standing crop showed a positive association. Random forest modelling further revealed that pond biomass, salinity, and feeding rate were important predictors of CO 2 , whereas CH 4 and N 2 O were primarily determined by water age and water source, respectively. Although this preliminary study was limited by the number of sampled farms and the temporal resolution of sampling, it cautiously proposes frequent water exchange, stocking-density optimization, carp integration, increased feeding frequency, and enhanced farmers’ knowledge as possible options to reduce emissions but warrants further longitudinal investigation.

Sumithion usage in aquaculture: benefit or forfeit? - Md Shahjahan; SM Majharul Islam; Alif Layla Bablee; Muhammad A.B. Siddik; Ravi Fotedar (Reviews in Aquaculture, 2021)
Sumithion is an organophosphate insecticide, extensively used to remove tiger bug from aquaculture ponds prior to the release of fish larvae. Its usage in aquaculture may initially assist in insect eradication; however, the harmful effects of sumithion may surpass the beneficial effects and may be alarming for the farmed fish and other aquatic organisms. This study summarizes the consequential effects of sumithion on the natural productivity in aquaculture ponds, and early development, physiological response, and reproductive functions of the farmed fish. Studies have found that sumithion adversely affects the natural production of phytoplankton, zooplankton and benthos, and reduces the hatching success with increased mortality, and morphological alterations in fish embryos and larvae. Fish haematological and biochemical alterations are also reported to be induced by the exposure to sumithion, as are variety of histopathological alterations and reproductive dysfunctions in exposed fish. Overall, this study is the first comprehensive overview of any insecticide which may advance our understanding of the rational and restricted use of insecticide in aquaculture operations.